Ultrasonographic signs as predictors of metastatic involvement in the axillary lymph nodes in breast cancer patients: from minimal changes to the appearance of the pathological lymph node. A retrospective analysis - Veverková, Lucia; Kolečková, Markéta; Vomáčková, Katherine; Zlámalová, Nora; Löwová, Ľübica (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2024)
INTRODUCTION: The aim of this study was to retrospectively analyse the ultrasound findings in the axillary lymph nodes in breast cancer patients with morphological changes that required biopsy. In most cases the morphological changes were minimal. MATERIALS AND METHODS: Between January 2014 and September 2019 examination of axillary lymph nodes with subsequent core-biopsy was performed in 185 breast cancer patients at the Department of Radiology. Lymph node metastases were detected in 145 cases, while in the remaining 40 cases benign changes or normal lymph node (LN) histology was observed. Ultrasound morphological characteristics and the sensitivity and specificity were evaluated retrospectively. Seven ultrasound characteristics were evaluated - diffuse cortical thickening, focal cortical thickening, absence of the hilum, cortical non-homogeneities, L/T ratio (longitudinal to transverse axis), type of vascularization and perinodal oedema. RESULTS AND CONCLUSION: It is a diagnostic challenge to recognize metastases in the lymph nodes with minimal morphological changes. The most specific signs are non-homogeneities in the cortex of the lymph node as well as the absence of fat hilum and perinodal oedema. Metastases are significantly more frequent in LNs with a lower L/T ratio, in LNs with perinodal oedema and with a peripheral type of vascularization. Biopsy of these lymph nodes is necessary to confirm or exclude metastases, especially if it affects the type of treatment.
Keywords: senioři; Breast Neoplasms; senioři nad 80 let; Retrospective Studies; Axilla; Middle Aged; lymfatické metastázy; Sensitivity and Specificity; Lymph Nodes; Adult; Lymphatic Metastasis; axila; Aged, 80 and over; ultrasonografie; ženské pohlaví; retrospektivní studie; Humans; lidé středního věku; lymfatické uzliny; senzitivita a specificita; nádory prsu; Ultrasonography; dospělí; Female; Aged; lidé